Optimization of Vehicle Polish Liquid Production Quantity at Son Polish Using Integer Programming - Aloysius Lionel Moise; Herlina Herlina (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
Son Polish is an industry that produces various liquid products that are useful for caring for the body and components in automotive vehicles. Although it has been established for a long time, Son Polish will only undergo the acquisition process for the first time in 2025. So that in its implementation, Son Polish does not have a production management system in determining the optimal daily production output by considering the capacity of the company's resources. Considering that Son Polish currently has 8 types of products, each of which has different resource needs, of course. This condition causes a deviation that occurs between the amount of production and consumer demand who have various types of products. Therefore, the purpose of this study is to determine the optimal combination of production amounts. Based on the results of the integer programming model using the branch and bound method which was completed using lingo software, a combination of Son Polish production was obtained by producing 3 batches of Son Spray, 2 batches of Son Jelly, 1 batch of Son Taro, 2 batches of Tire Polish, 2 batches of Son Black, 1 batch of Son R, 1 batch of Haalus Compound and 1 batch of Rough Compound. With a profit obtained of Rp. 136,365,000.00/month or equivalent to Rp. 5,454,600.00/day.